Correlazioni tra proprietá reologiche, struttura e processabilitá di blend di LLDPE/LDPE - Ferri, Dino <1968> (Alma Mater Studiorum - Università di Bologna, 2010)
Polymer blends constitute a valuable way to produce relatively low cost new materials. A still open question concerns the miscibility of polyethylene blends. Deviations from the log-additivity rule of the newtonian viscosity are often taken as a signature of immiscibility of the two components. The aim of this thesis is to characterize the rheological behavior in shear and elongation of five series of LLDPE/LDPE blends whose parent polymers have been chosen with different viscosity and SCB content and length. Synergistic effects have been measured for both zero shear viscosity and melt strength. Both SCB length and viscosity ratio between the components have been found to be key parameters for the miscibility of the pure polymers. In particular the miscibility increases with increasing SCB length and with decreasing the LDPE molecular weight and viscosity. This rheological behavior has significant effects on the processability window of these blends when the uni or biaxial elongational flows are involved. The film blowing is one of the processes for which the synergistic effects above mentioned can be crucial. Small scale experiments of film blowing performed for one of the series of blends has demonstrated that the positive deviation of the melt strength enlarges the processability window. In particular, the bubble stability was found to improve or disappear when the melt strength of the samples increased. The blending of LDPE and LLDPE can even reduce undesired melt flow instability phenomena widening, as a consequence, the processability window in extrusion. One of the series of blends has been characterized by means of capillary rheometry in order to allow a careful morphological analysis of the surface of the extruded polymer jets by means of Scanning Electron Microscopy (SEM) with the aim to detect the very early stages of the small scale melt instabilty at low shear rates (sharksin) and to follow its subsequent evolution as long as the shear rate was increased. With this experimental procedure it was possible to evaluate the shear rate ranges corresponding to different flow regions: smooth extrudate surface (absence of instability), sharkskin (small scale instability produced at the capillary exit), stick-slip transition (instability involving the whole capillary wall) and gross melt fracture (i.e. a large scale "upstream" instability originating from the entrance region of the capillary). A quantitative map was finally worked out using which an assessment of the flow type for a given shear rate and blend composition can be predicted.